ENERGY-DISTRIBUTIONS IN THE CN(CHI-2-SIGMA+) FRAGMENT FROM THE INFRARED MULTIPLE-PHOTON DISSOCIATION OF CF3CN - A COMPARISON BETWEEN EXPERIMENTAL RESULTS AND THE PREDICTIONS OF STATISTICAL-THEORIES - Beresford, J; Hancock, G; Macrobert, A; Catanzarite, J; Radhakrishnan, G; Reisler, H; Wittig, C (1983)
Rotational and vibrational distributions in CN(X2Σ+) produced in the collisionless infrared multiple-photon dissociation (MPD) of CF3CN have been measured by laser-induced fluorescence. Both distributions appear Boltzmann, and may be assigned "temperatures" of Tvib = 2400 ± 200 K and Trot = 1200 ± 100 K. Phase-space theory (PST) and statistical adiabatic-channel theory (SACT) have been used to calculate the CN internal excitations. Both theories predict Boltzmann-like behaviour to within the available experimental resolution, with this being more pronounced in calculations using a distribution of CF3CN energies above dissociation threshold (as expected for the case of multiple-photon absorption) than in those using a single excited level of CF3CN. PST consistently predicted similar values of Tvib and Trot, in contrast to the observations. SACT calculations, however, reproduced the experimental temperatures using a parameter α which describes the range of the angular potential between separating fragments and whose value lies in the range 0.5-1.0 Å-1. The data are also qualitatively consistent with a simple model which assumes that fragment rotational and translational excitations derive from parent R,T motions in combination with the kinetic energies of those parent vibrations which are converted to product R,T excitations. Thus, statistical theories other than PST can be used to explain the experimental results, and such comparisons offer insight into details of the dissociation process.